Assessment of Quality of Life and Supporting Structures in Implant Retained Mandibular Overdenture: A 5-Year Cohort Study - Abd El Rahim NS; Ashour AA (Dove Medical Press, 2022)
Neveen S Abd El Rahim,1,2 Asmaa A Ashour1 1Department of Removable Prosthodontics, Faculty of Dental Medicine for Girls, Al- Azhar University, Cairo, Egypt; 2Department of Removable Prosthodontics, College of Dentistry, Taibah University, Medina, Saudi ArabiaCorrespondence: Asmaa A Ashour, Department of Removable Prosthodontics, Faculty of Dental Medicine for Girls, Al- Azhar University, Nasr City, Cairo, Egypt, Tel +201284048535, Email aasmaa@azhar.edu.egAim: To assess oral health-related quality of life (OHRQoL), marginal bone loss (MBL), and changes in soft tissue including probing pocket depth and implant stability in 2 implants retained mandibular overdentures during 5 years follow-up periods.Methods: Forty completely edentulous patients with age 51- 64 years were recruited for that longitudinal cohort study. Complete dentures were performed for all participants. Two implants (3.6 × 11.5 mm) were installed in the canine areas of the mandible. OHRQoL and MBL measures were performed every 1 year for 5 years, while clinical measures were made every 6 months for 60 months. Data were examined using repeated ANOVA and Friedman test.Results: Thirty-seven patients had 74 implants; with mean age 56 ± 3.6 years; 43% females (n = 16) and 57% males (n = 21) accomplished the study. There were statistically significant differences in OHRQoL, MBL, and changes in soft tissue, including probing pocket depth and implant stability in 2 implants retained mandibular overdentures during 5 years follow-up periods, p ≤ 0.05.Conclusion: Mandibular overdentures retained by 2 implants provide a positive long-term effect on OHRQoL, MBL, probing pocket depth, and implant stability.Keywords: implant-retained overdenture, quality of life, marginal bone loss, pocket depth, COVID-19